2016
DOI: 10.2341/15-010-l
|View full text |Cite
|
Sign up to set email alerts
|

Enamel Surface Changes After Exposure to Bleaching Gels Containing Carbamide Peroxide or Hydrogen Peroxide

Abstract: All six bleaching gels effectively bleached the enamel specimens independent of their concentration of peroxide. Gels with low peroxide concentration and longer contact time negatively affected the enamel surface.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
50
0
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(60 citation statements)
references
References 26 publications
3
50
0
7
Order By: Relevance
“…One possible factor that may have contributed to the reduction of enamel microhardness was the contact time of fluoride free bleaching gel with enamel surface which may have disrupted the balance between demineralization caused by the bleaching agent and the remineralization caused by artificial saliva. 27,33,34 These findings are in agreement with our SEM analyses, where was observed an irregular surface with depressions, porosity, and increased depth of enamel grooves. 13 Other studies also observed these alterations and the enamel microhardness decrease when low carbamide peroxide (10 or 15%) concentrations were used for long treatment times.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…One possible factor that may have contributed to the reduction of enamel microhardness was the contact time of fluoride free bleaching gel with enamel surface which may have disrupted the balance between demineralization caused by the bleaching agent and the remineralization caused by artificial saliva. 27,33,34 These findings are in agreement with our SEM analyses, where was observed an irregular surface with depressions, porosity, and increased depth of enamel grooves. 13 Other studies also observed these alterations and the enamel microhardness decrease when low carbamide peroxide (10 or 15%) concentrations were used for long treatment times.…”
Section: Discussionsupporting
confidence: 90%
“…13,25,26 One reason for this may be the increasing of contact time of low concentrated bleaching gels with tooth surface, which promoted surface changes in concentration of ions calcium and phosphate, degradation of organic matrix, erosion, porosities, and depressions. 25,27 The gel used in this study was maintained in contact with enamel surface 4 hours/ day during two weeks. Additionally, the gel contains carbopol as thickening agent which has been suggested that can also adversely affect dental enamel.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the introduction of the Nightguard Vital Bleaching technique using 10% carbamide peroxide [2], studies have been conducted to evaluate the possible effects produced on dental tissues during and after whitening procedures. Despite the favorable results achieved with bleaching treatment [3,4], there are many controversies as regards its adverse effects [5] such as dental sensitivity during treatment, a decrease in enamel surface hardness [4,6,7], volume and mineral loss [8] and morphologic alterations after exposure to bleaching agents [9][10][11]. The controversies presented in the literature are not only related to the results found by different research groups, but also to the significant variety of methods that have been used to investigate the possible effects of bleaching agents on the physical and chemical properties of enamel [12][13][14][15].…”
Section: O R I G I N a L A R T I C L Ementioning
confidence: 99%
“…Vital tooth bleaching is considered to be a conservative esthetic treatment modality to improve tooth color because no sound tooth structure is removed. Although adverse effects to enamel surface properties such as reduction in hardness [2], change in surface morphology [3] and increased susceptibility to abrasion/erosion [4] have been reported, the wide variety of different bleach concentrations and application methods, as well as different study designs, have contributed to equivocal conclusions. In general, the effects of tooth bleaching on the enamel surface have been considered to be minor or clinically insignificant [5, 6].…”
Section: Introductionmentioning
confidence: 99%